Desert Peak EGS: Mechanisms influencing permeability evolution investigated using dual-porosity simulator TFReact - Benato, Stefano; Taron, Joshua (Geothermics, 2016)
•A THM simulation approach is proposed to model geothermal stimulation treatments.•Tensile vs. shear mechanisms show distinct impact on the evolution of permeability.•Model reveals alternative stimulation choices for enhanced permeability gain. The reservoir response associated with selected phases of the hydraulic stimulation conducted as part of the 2010–2013 Desert Peak Enhanced Geothermal System (EGS) project was investigated using the dual-porosity numerical simulator TFReact. The code couples the solid mechanics (M) analyses of FLAC3D with the multiphase, non-isothermal and reactive capabilities (THC) of TOUGHREACT, and allows for a comprehensive investigation of the major thermal-hydraulic-mechanical-chemical (THMC) physical processes occurring in deep, tight rock masses subject to circulation of pressurized fluids. Numerical simulations were performed to determine: (a) pore pressure diffusion and stress field modifications, (b) development of mechanical deformation, and, above all, (c) relative impact of tensile vs. shear deformation on the evolution of the reservoir permeability. A three-well reservoir model was implemented to account for the combined influence of concurrent injection in wells 27–15 (EGS well), 22–22 and 21–2 (active injectors). This study simulated selected stimulation treatments carried out from 914 to 1067m depth (shallow stimulation interval) and from 914 to 1771m depth (extended stimulation interval). Alternative hydraulic stimulation schemes/scenarios (by assuming diverse varying injectate properties and injection durations) were modeled over the two stimulation intervals to test if and how the final permeability could have been further improved. Simulated permeability modifications appear to be predominantly governed by thermo-hydro-mechanical dilation (elastic) during stimulation of the shallow interval and by hydro-mechanical deformation (inelastic shear) during stimulation of the extended interval. Inelastic shear deformation delivers higher permeability gains, and in the shortest time, when hydraulically conductive and well-oriented features are targeted with the stimulation treatment. TFReact simulations combined with a detailed site conceptualization and microseismicity interpretation, provide further understanding of injection-induced mechanisms.